A conceptual design of shock-eliminating clover combustor for large scale scramjet engine. (January 2017) - Sun, Ming-bo; Zhao, Yu-xin; Zhao, Guo-yan; Liu, Yuan
Abstract: A new concept of shock-eliminating clover combustor is proposed for large scale scramjet engine to fulfill the requirements of fuel penetration, total pressure recovery and cooling. To generate the circular-to-clover transition shape of the combustor, the streamline tracing technique is used based on an axisymmetric expansion parent flowfield calculated using the method of characteristics. The combustor is examined using inviscid and viscous numerical simulations and a pure circular shape is calculated for comparison. The results showed that the combustor avoids the shock wave generation and produces low total pressure losses in a wide range of flight condition with various Mach number. The flameholding device for this combustor is briefly discussed. Highlights: A shock-eliminating clover concept is proposed for large scale scramjet. Streamline tracing technique is used with a parent flowfield obtained by MOC. Tests show the combustor produces low aerodynamic loss in a wide range. Flameholding device for this combustor is briefly discussed.